2016
DOI: 10.1175/jcli-d-16-0377.1
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Precipitation Indices over China in CMIP5 Models. Part II: Probabilistic Projection

Abstract: The present article is the second part of a study on the extreme precipitation indices over China in CMIP5 models that perform a probabilistic projection of future precipitation indices with reference to the period 1986–2005. This is realized with a rank-based weighting method. The ranking of the 25 models is done according to their performance in simulating rainfall indices in present-day climate. Such weights are used to form a weighted ensemble for future climate projection. Results show that, compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 42 publications
8
55
0
Order By: Relevance
“…The continuous supply of water vapor is an important factor for extreme precipitation (Li, Jiang, et al, 2016;Zhao et al, 2018;Zhao, Xu, Liu et al, 2019). To investigate the water vapor transport associated with extreme precipitation over the NCP in midsummer, the vertically integrated water vapor fluxes are calculated as follows:…”
Section: Vertically Integrated Water Vapor Fluxmentioning
confidence: 99%
“…The continuous supply of water vapor is an important factor for extreme precipitation (Li, Jiang, et al, 2016;Zhao et al, 2018;Zhao, Xu, Liu et al, 2019). To investigate the water vapor transport associated with extreme precipitation over the NCP in midsummer, the vertically integrated water vapor fluxes are calculated as follows:…”
Section: Vertically Integrated Water Vapor Fluxmentioning
confidence: 99%
“…Some studies have found increases in the intensity and probability of extreme precipitation over China in the future with global warming (Feng et al, ; W. Li et al, ; W. Li, Jiang, et al, ; Zhou et al, ). However, few studies have focused on the timing of the emergence of climate change signal from natural variability.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found increases in the intensity and probability of extreme precipitation over China in the future with global warming (Feng et al, 2011;W. Li et al, 2016;W.…”
Section: Introductionmentioning
confidence: 99%
“…The time-slice method can describe climate change under conditions of constant greenhouse gas concentrations into the future and then provide guidance for mitigation and adaptation strategies for certain periods (Allen and Ingram, 2002;Chen, 2013;Li et al, 2016). However, different models result in different global temperature responses for a given year because of climate sensitivity and other feedback processes.…”
mentioning
confidence: 99%